Naegleria australiensis isolated from a wastewater treatment station in Santiago Island, Cape Verde. (2nd March 2023) - Sousa-Ramos, Djeniffer; Reyes-Batlle, María; Bellini, Natalia Karla; Rodríguez-Expósito, Rubén Leocadio; Piñero, José Enrique; Lorenzo-Morales, Jacob
Abstract: Despite the Naegleria genus being isolated from different natural environments such as water, soil, and air, not all Naegleria species are capable of causing infections in humans, and they are capable of completing their life cycle in environmental niches. However, the presence of this genus may suggest the existence of one of the highly pathogenic free-living amoeba (FLA) species: Naegleria fowleri or the brain-eating amoeba. This facultative parasitic protozoon represents a risk to public health, mainly related to domestic and agricultural waters. In this research, our main objective was to determine the existence of pathogenic protozoa in the Santa Cruz wastewater treatment plant, Santiago Island. Using 5 L of water we confirmed the presence of potentially pathogenic Naegleria australiensis, being the first report on Naegleria species in Cape Verde. This fact demonstrates the low efficiency in the treatment of wastewater and, consequently, a potential threat to public health. Nevertheless, more studies will be needed for the prevention and control of possible infections in this Macaronesian country. HIGHLIGHTS: This is the first report on potentially pathogenic Naegleria species in Cape Verde. The wastewater treatment stations are a vital resource for the improvement of water use in several arid countries. Due to climate change, surface water temperatures are rising, being a susceptible niche to be colonized by pathogenic protozoa. The environmental presence of these species represents an important public health concern. Graphical Abstract